Potential development of halal tourism in improving people's welfare in the Selayar Islands Regency - Ashari, Wiwin; Suarni, Agusdiwana; Rahmah, Sahidah (Jurnal Ekonomi Balance, 2022)
This study aims to find out how the potential for developing halal tourism in improving the welfare of the people in the Selayar Islands Regency is. The type of research used in this research is field research that produces descriptive data in the form of written or oral data of people (informants) and observed behavior. While the data research techniques used in this study were interviews, observations (observations), and documentation. The results obtained from this study are how the potential for developing halal tourism in improving the welfare of the people in the Selayar Islands Regency is because currently there is no halal tourism object developed by the Selayar Islands Regency Tourism Office. Based on the results of observations and interviews in the Sunari coastal tourism area, it is still relatively new and the Selayar Islands Regency Tourism Office will continue to communicate with the village government for the development of the Sunari beach tourism area, Selayar Islands Regency. Although the tourism office has not taken any steps to get there, the local tourism office supports the development of halal tourism in the Sunari beach tourism area, Selayar Islands Regency. For visitor responses regarding the potential for developing halal tourism in improving the welfare of the community in Bulukumba Regency, around 99% of visitors to Sunari Beach tourism in Selayar Islands Regency said they agreed because they saw the majority of the community were Muslim, especially in Selayar Islands Regency there was no halal tourism